2018
DOI: 10.1016/j.atherosclerosis.2018.08.042
|View full text |Cite
|
Sign up to set email alerts
|

Progranulin in the hematopoietic compartment protects mice from atherosclerosis

Abstract: We conclude that hematopoietic progranulin deficiency promotes diet-induced atherosclerosis in Ldlr mice, possibly due to increased exophagy-mediated cholesterol uptake. Circulating progranulin was unable to prevent the increased lesion development, consistent with the importance of progranulin acting via cell-autonomous or local effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 51 publications
3
11
0
Order By: Relevance
“…The finding of lipid droplet containing microglia in GRN −/− mice is corroborated by a recent study which showed that cultured progranulin-deficient macrophages exhibited increased foam cell formation, i.e. lipid droplet accumulation, compared to wild type macrophages 49 . In addition, a recent study reported that loss of GRN leads to intracellular and intra-lysosomal accumulation of long polyunsaturated triacylglyerides 50 in the brains of humans and mice.…”
Section: Discussionsupporting
confidence: 58%
“…The finding of lipid droplet containing microglia in GRN −/− mice is corroborated by a recent study which showed that cultured progranulin-deficient macrophages exhibited increased foam cell formation, i.e. lipid droplet accumulation, compared to wild type macrophages 49 . In addition, a recent study reported that loss of GRN leads to intracellular and intra-lysosomal accumulation of long polyunsaturated triacylglyerides 50 in the brains of humans and mice.…”
Section: Discussionsupporting
confidence: 58%
“…Although previously identified in aging [ 74 ] and AD [ 18 ], microglia in GRN knockout mouse models display severe accumulation of lipids, significant defects in phagocytosis, increased reactive oxygen species and elevated pro-inflammatory cytokines [ 74 ]. This extends previous research showing microglial lipofuscin accumulation [ 75 ] and foam cell formation in GRN-deficient macrophages [ 76 ] and accumulation of triacylglycerides in fibroblast and lysosomal lipidomes in humans and mice with GRN mutations [ 77 ]. Dystrophy was more severe in FTLD- C9orf72 cases in all regions compared with controls but varied considerably across cases within this group.…”
Section: Discussionsupporting
confidence: 89%
“…The finding of lipid droplet containing microglia in GRN -/mice is corroborated by a recent study which showed that cultured progranulin-deficient macrophages exhibited increased foam cell formation, i.e. lipid droplet accumulation, compared to wild type macrophages 78 . In addition, a recent study reported that loss of GRN leads to intracellular and intra-lysosomal accumulation of long polyunsaturated triacylglyerides 79 in the brains of humans and mice.…”
Section: Lam In Neurodegenerationsupporting
confidence: 55%